IBM Malaysia: a study on the public sector market / Mashitoh Arshad - Arshad, Mashitoh (1991)
Government legislation plays an important role in information technology industry decision making. Organizations in the public sector are designed to be rational. However , the individuals in the organisations have their own ambitions, fears, fantasies and emotions, and managements in different organizations have their own style. The salient global trends of Information Technology are as-follows: # Information Technology is permeating into all other economic sectors and act as a key competitive tool in these sectors. # Information technology production and services is becoming the biggest and fastest growing economic sector. # Competition in Information Technology industries is becoming increasingly global. # Strong government intervention and support of national information technology industries is increasingly evident. The identification of problem areas in the public sector in computerization projects could perhaps point out what IBM need for planning not only customer targets but also competitors' targets at various level of government ministries and non-profit markets that buy product and services in order to provide public services or transfer these products and services to others who need them.